2010
DOI: 10.4161/auto.6.6.12397
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic analysis revealed association of aberrant ROS signaling with suberoylanilide hydroxamic acid-induced autophagy in Jurkat T-leukemia cells

et al.

Abstract: (2010) Proteomic analysis revealed association of aberrant ROS signaling with suberoylanilide hydroxamic acid-induced autophagy in Jurkat T-leukemia cells, Autophagy,6:6,[711][712][713][714][715][716][717][718][719][720][721][722][723][724]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 59 publications
5
75
0
Order By: Relevance
“…Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo. Further functional analysis showed that inhibition of autophagy markedly increased quercetin-induced apoptotic cell death, suggesting that quercetin-induced autophagy plays a protective role in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo. Further functional analysis showed that inhibition of autophagy markedly increased quercetin-induced apoptotic cell death, suggesting that quercetin-induced autophagy plays a protective role in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…Accumulating evidence suggested a paradoxical role of autophagy in control of cell death and survival under various stimulus conditions. [31][32][33][34][35][36] To determine the in the cytoplasm of both AGS and MKN28 cells treated with quercetin. To further characterize the membrane-associated vacuoles, acridine orange staining was used to analyze the formation of acidic vesicular organelles (AVOs), a main feature of autophagy.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…39 Further experiments with acridine orange and MDC staining also confirmed SAHA-induced autophagy in GSCs, similar to results of studies on hepatocellular carcinoma and T-leukemia cells. 21,22 A possible explanation for the increase in SAHA-mediated autophagy-induction is that SAHA inactivates AKT-MTOR signaling by dephosphorylation of Ser473 and MTOR Ser2448. Depletion of autophagy-related genes or pharmacological inhibition resulted in SAHA-induced apoptosis at the early phase, whereas cotreatment of rapamycin provided a protective effect against the activation of caspase by overdose induction of SAHA treatment, suggesting that SAHAinduced autophagy functions as a prosurvival mechanism to mitigate SAHA-induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that SAHA could induce autophagy in certain types of cancers, including hepatocellular carcinoma and T-leukemia cells, 21,22 and we hypothesized that SAHA causes autophagy in GSCs. Transmission electron microscopy (TEM) is a standard method to reliably detect autophagy.…”
Section: Saha-induced Autophagy In Gscs Is Dependent On Inhibition Ofmentioning
confidence: 99%
See 1 more Smart Citation